A typical antipsychotic treatment induced gradually expanding white matter alterations in healthy individuals with persistent auditory verbal hallucinations—an artificially controlled pilot study. (3rd June 2021) - Lin, Xiaodong; Li, Gongying; Ji, Feng; Cheng, Langlang; Chen, Guangdong; Zhang, Wei; Su, Zhonghua; Zhang, Zhenqing; Wang, Wenqiang; Zhou, Chunhua; Xu, Yong; Zhuo, Chuanjun
Abstract: Objective: The aim of this study was to explore the effects of atypical antipsychotics (AaPs) on brain white matter (WM) tracts in healthy individuals with auditory verbal hallucinations (Hi-AVHs). Methods: We analyzed neuroimaging, AVH symptoms, and cognitive assessment data obtained from 39 Hi-AVHs who reported being distressed by persistent AVHs and volunteered to receive AaP treatment. We used tract-based spatial statistics (TBSS) and t tests to explore AaP pharmacotherapy effects on AVH symptoms and brain WM alterations in Hi-AVH subjects. Results: TBSS and t tests revealed WM alterations after AaP treatment, relative to pretreatment observations. Although AaPs alleviated AVH symptoms, WM alterations in these subjects expanded over 8 months of AaP treatment, encompassing most major WM tracts by the end of the observation period, including the corpus callosum, arcuate fasciculus, cortico-spinal tracts, anterior commissure, and posterior commissure. Conclusions: The worsening of AaP-associated WM alterations observed in this study suggest that AaPs may not be a good choice for the treatment of Hi-AVHs despite their ability to alleviate AVHs.